Latino Health Behavior: An Exploratory Analysis of Health Risk and Health Protective Factors in a Community Sample. Issue 1 (January 2020) - Gast, Julie; Peak, Terry; Hunt, Anne
Background. Demographic and cultural factors have been found to affect health behaviors in Latinos in both positive and negative ways, but few studies have examined the impact of culture and adherence to machismo norms on health behaviors in a mixed gender community sample of Latinos. Of particular interest was if positive ( caballerismo ) or negative aspects of machismo would affect Latino health behaviors. Methods. A paper survey was given to a community sample of Latinos in northern Utah to explore the variables that affect both health promoting and health risking behaviors in this cross-sectional study (final N = 144 participants). Results. Life satisfaction, self-reported health, health insurance status, language preference, and gender were significantly related to overall health score. Surprisingly, the cultural variables of fatalism, machismo, and caballerismo were nonsignificant in all analyses. Conclusion. Access to health care mediated by health insurance and self-reported health status may be the most effective way to encourage Latinos to engage in protective health behaviors.